How Does Turning to AI for Companionship Predict Loneliness and Vice Versa? - Folk, Dunigan; Dunn, Elizabeth (Psychological Science, 2026)
Advances in AI have enabled chatbots to provide warm, personalized support. Yet little is known about the long-term consequences of AI companionship. Across a 12-month longitudinal study with more than 2,000 adults from four Western countries, we examined the bidirectional relationships between social chatbot use and loneliness.We found evidence that increased social chatbot use predicted increased loneliness, using a single-item measure of emotional isolation. When we used a broader and more stable measure of social connection, we found evidence that feeling less socially connected predicted subsequent increases in social chatbot use; however, chatbot use did not significantly predict decreases in social connection. Taken together, these findings provide initial evidence that being lonely may spur people to seek companionship through chatbots but that such use may, over time, exacerbate feelings of loneliness. We urge caution, however, in drawing strong conclusions given the exploratory nature of our analyses.